2019
DOI: 10.15694/mep.2019.000021.1
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong learning practices and leisure-time exercise habits of academic and community-based physicians

Abstract: Objective: Physicians are required to be lifelong learners for the provision of quality patient care. At the same time, physician wellbeing is a critical component in the delivery of such care. This study was designed to examine: (1) lifelong learning practices and leisure-time exercise habits of academic and community-based physicians; and (2) associations of leisure-time exercise with work engagement, exhaustion, and professional life satisfaction. Methods:Using an online survey, quantitative data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Even so, these CME licensure requirements may not be sufficient. Workplace interactions with colleagues, on‐the‐job database “research,” clinical teaching, and attendance at conferences were strongly valued by physicians as methods of “lifelong learning” and are not always reflected in all certification requirements for maintaining licensure 129 . The barriers in radiology to continuing medical education include insufficient time or financial support, lack of interest or perceived benefit, and lack of awareness of CME opportunities 130 …”
Section: What Makes Molecular Pathology Susceptible To Unjust Distrib...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, these CME licensure requirements may not be sufficient. Workplace interactions with colleagues, on‐the‐job database “research,” clinical teaching, and attendance at conferences were strongly valued by physicians as methods of “lifelong learning” and are not always reflected in all certification requirements for maintaining licensure 129 . The barriers in radiology to continuing medical education include insufficient time or financial support, lack of interest or perceived benefit, and lack of awareness of CME opportunities 130 …”
Section: What Makes Molecular Pathology Susceptible To Unjust Distrib...mentioning
confidence: 99%
“…Workplace interactions with colleagues, on-the-job database "research," clinical teaching, and attendance at conferences were strongly valued by physicians as methods of "lifelong learning" and are not always reflected in all certification requirements for maintaining licensure. 129 The barriers in radiology to continuing medical education include insufficient time or financial support, lack of interest or perceived benefit, and lack of awareness of CME opportunities. 130 Maintaining current knowledge of oncology care is even more challenging, with 30 new cancer drugs, 45 new adjunct therapies, and 1 biosimilar being approved in 2020 alone.…”
Section: Regional Disparitiesmentioning
confidence: 99%
“…As such, these activities and habits should be encouraged, supported, and promoted within institutional culture and health systems in general". (Babenko O, Ding M, Koppula S, 2019) Wu and associates suggested that training to upskill feedback giving is a feasible strategy to increase receptiveness of participants to peers' feedback and activate participants' motivation to make the immediate and continuous behavior changes on giving behavior-specific peer-feedback on holistic-care. (Wu S, Yang Y, Shulruf B, Yang L, et al, 2019) Yuan and associates' study "indicated that FAIMER's faculty development program had a positive influence in advancing several aspects in health professions continuing education.…”
Section: Research Articlesmentioning
confidence: 99%
“…As such, these activities and habits should be encouraged, supported, and promoted within institutional culture and health systems in general”. ( Babenko O, Ding M, Koppula S, 2019 )…”
Section: Submissions and Synopsismentioning
confidence: 99%